Diagnostic utility of somatosensory evoked potentials in chronic polyradiculopathy without electrodiagnostic signs of peripheral demyelination. Issue 1 (26th November 2015) - Devic, Perrine; Petiot, Philippe; Mauguiere, François
ABSTRACT: Introduction: Diagnosis of chronic inflammatory demyelinating polyneuropathy (CIDP) remains uncertain when nerve conduction studies (NCS) fail to show demyelination. Methods: We conducted a retrospective study of patients who presented with clinical criteria of CIDP in whom electrodiagnostic (EDx) criteria of definite or probable CIDP were missing [axonal sensorimotor neuropathy ( n  = 23), normal EDx with pure sensory presentation ( n  = 3)]. All patients received immunomodulatory treatment. Twenty‐six patients were evaluated with somatosensory evoked potentials (SSEPs), MRI of spinal roots, cerebrospinal fluid analysis, and/or nerve biopsy. Diagnosis of CIDP was considered to be confirmed in patients who responded to immunotherapy. Results: Twenty‐two of 26 patients (85%) had SSEPs reflecting abnormal proximal conduction in sensory fibers, including 14 who had only clinical and SSEP data in favor of CIDP. SSEPs were abnormal in 16 of 20 responders (80%) to immunotherapy. Conclusion: SSEP recording contributes to the diagnosis of CIDP when nerve conduction studies fail to detect peripheral demyelination. Muscle Nerve 53 : 78–83, 2016